A Sociolinguistics Study Of English Borrowings Used InPanjebar Semangat Magazine. January, 2011 Edition - Tamtomo, Yuli, Drs. Maryadi, MA, Drs. Agus Wijayanto, Ph.D (2013)
This descriptive qualitative research paper is aim to describe and elaborate the kinds and ways of English borrowing used in Panjebar Semangat magazine on January, 2011 edition. The data of this research are words, phrases, noun phrases and sentences containing the English borrowing in Panjebar Semangat magazine. There are four magazine in each month because the magazine is published every weeks on Saturday. The magazine has 29 rubrics consist of 54 pages. In collecting the data, the researcher uses documentation method. The researcher uses Haugen's theory (Katamba, 2007: 192) in analyzing the kinds of borrowing, and Katamba (1997: 191) in analyzing the ways of borrowings. The result of this research paper are three points, they are; (1) two kinds of English borrowings used in Panjebar Semangat magazine; they are loanword and loan shift, and (2) two ways of English borrowings; they are direct and indirect borrowings, and (3) kinds of sound replacing of English borrowings.